Analysis of glutathione-S-transferases from larvae of Galleria mellonella (Lepidoptera, Pyralidae) with potential alkaloid detoxification function - Venthur, Herbert; Lizana, Paula; Manosalva, Loreto; Rojas, Valentina; Godoy, Ricardo; Rocha, Adonis; Aguilera, Iván; Palma-Millanao, Rubén; Fajardo, Victor; Quiroz, Andrés; Mutis, Ana (Frontiers in Physiology, 2022)
The greater wax moth, Galleria mellonella, is a global pest for beehives, doing damage in the larval stage. Although a significant number of studies have reported on larvae and adults, to date no effective pest control has been implemented. In this study, we tested larval resistance to alkaloids from Berberis microphylla, and the objective was to identify enzymes that participate in alkaloid detoxification through enzymatic assays, bioinformatics analysis and qRT-PCR. Findings suggest glutathione-S-transferases (GSTs), from an increased metabolic mechanism, are responsible for alkaloid detoxification rather than cytochrome P450 (CYP), carboxylesterases (CarE). A bioinformatics analysis from transcriptome data revealed 22 GSTs present in both G. mellonella larvae and adults. The qRT-PCR experiments corroborated the presence of the 22 GSTs in larvae, where GST8 and GST20 stood out with the highest expression after berberine treatment. Structural information around GST8 and GST20 suggests that GST8 could bind berberine stronger than GST20. These findings represent an important advance in the study of detoxification enzymes in G. mellonella, expanding the role of delta-class GSTs towards alkaloids. Likewise, GST inhibition by alkaloid analogs is proposed in the framework of integrated pest management strategies.